Ultrasonography-guided Cannula Method for Hyaluronic Acid Filler Injection with Evaluation using Laser Speckle Flowgraphy. Issue 4 (April 2018) - Iwayama, Takanori; Hashikawa, Kazunobu; Osaki, Takeo; Yamashiro, Kenjiro; Horita, Nobuyuki; Fukumoto, Takeshi
Abstract : Summary: Hyaluronic acid (HA) is present in the connective tissues of the skin and decreases with age. HA fillers are popular as facial rejuvenation treatments. They are generally considered safe; however, complications, such as cutaneous necrosis and blindness due to vascular embolism, sometimes occur. Because vascular embolisms are likely associated with the deep placement of HA fillers, a strategy that involves injection into superficial regions (the conventional method) is commonly used to reduce risks. However, deep injections to achieve revolumization are becoming common, even in high-risk areas for intravascular infusion. We aimed to study the usefulness of the ultrasonography-guided cannula method for preventing intravascular infusion of HA fillers. An HA filler was injected into the region just under the dermis on the left side of the face of a 38-year-old man using the conventional method, and another HA filler was injected into the periosteum on the right side using the ultrasonography-guided cannula method. The skin blood flow on both sides was compared using laser speckle flowgraphy (LSFG). The ultrasonography-guided method was successful in detecting the cannula and the blood vessel, and the HA filler was safely injected into a deep region. Using LSFG, a difference in skin blood flow between the 2 methods was detected. The ultrasonography-guided cannula method was effective in aiding the safe injection of an HA filler in a deep high-risk area and maintained skin blood flow. LSFG may be adopted to evaluate skin blood flow after HA filler injections.